Impact of COVID-19 on breastfeeding, 2021. - Reyes-Serrano, Bertha Nathaly (2023)
Introduction. As we know, breastfeeding has been one of the richest sources of nourishment since ancient times, providing a wide range of antimicrobial, anti-inflammatory, immunomodulatory agents, leukocytes, and other properties that contribute to the newborn's nutrition and proper development from the first suckling, aiding their adaptation to extrauterine life. That is why it has been prioritized and determined that breastfeeding should continue normally as long as the mother complies with all biosecurity protocols. Objetive. To understand how the COVID-19 virus has impacted breastfeeding and what preventive and promotional measures have been implemented to maintain the golden hour. Materials and Methods. A qualitative investigation was carried out during 2021, conducting a narrative review through documentary study of references, including systematic reviews and original articles. The search was performed using scientific databases such as PubMed, Medline, Science Direct, Bvs, and Google Scholar, using the following keywords and connectors: Lactancia materna OR Breastfeeding OR Lâctancia Materna AND Covid OR Covid 19 OR Covid19; Breastfeeding AND Covid-19, and articles in English, Spanish, and Portuguese. Results. Breastfeeding with suspected or confirmed COVID-19 and the benefits of colostrum therapy: Breastfeeding should be individualized in each case of mothers who are COVID-19 positive, as to date, no contraindications have been reported recommending its discontinuation, but always prioritizing the newborn's health. On the other hand, colostrum therapy should be used as a means of protection for the newborn. Conclusions. Breastfeeding should be initiated within the first hour of life, facilitating skin-to-skin contact, but with recommended biosecurity measures such as wearing a mask at all times, thorough handwashing before having contact with the newborn, prior breast hygiene, disinfecting nearby surfaces, and if milk expression is necessary, ensuring thorough disinfection of all equipment. These preventive measures are being implemented during labor and in rooming-in. The promotion of breastfeeding should continue, as the benefits it provides to the newborn outweigh the risks of virus transmission.